Model Predictive Control for Omnidirectional Small Size Robot with Motor and Non-Slipping Constraints - Pinheiro, Felipe; Máximo, Marcos; Yoneyama, Takashi (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS), 2019)
Model Predictive Control for Omnidirectional Small Size Robot with Motor and Non-Slipping Constraints